Determining the Leadership Order of the Clinically Responsible Nurse Working in a University Hospital - Yücel, Ilknur; Cihangiroğlu, Nuray (Nursing and Health Sciences Journal (NHSJ), 2024)
This study aims to determine the leadership orientations of clinical chief nurses. In the descriptive study, the G-Power 3.1.9.4 program was used to calculate the sample size and the number of people planned to be included in the study was calculated as 50 with 5% error and 95% power. In this direction, all (50) clinical nurses working in a university hospital between 10.05.2023 and 30.05.2023 will form the study sample group. The data of the study will be collected from individuals with a socio-demographic "Leadership Orientation Questionnaire" prepared by the researchers. 84.6% of the participants were female and 15.4% were male. While 89.7% of the participants are married, 10.3% are single. While 56.4% of them are graduates, 43.6% of them are undergraduates. 46.2% of the participants have been in management for 0-5 years, 28.2% for 10 years and above, and 25.6% for 5-10 years. While the participants' human-oriented leadership behavior score average was 7.79, the minimum score was 3 and the maximum score was 12. While the task-oriented behavior average score was 12.62, the minimum score was 4 and the maximum score was 19. While the leadership orientation total score average was 20.41, the minimum score was 7, and the maximum score was 27. As a result of this study, there is no significant difference between the sub-dimensions of the leadership orientation scale and age, gender, marital status, educational status, duration of work in the profession, and management process. Therefore, extra pieces of training should be planned for responsible nurses, taking into account clinical leadership. There are few studies on this subject in the literature. It is recommended to increase the studies.